Different miniaturized extraction methodologies followed by GC–MS/MS analysis for the determination of UV filters in beach sand. Issue 17 (31st July 2018) - Vila, Marlene; Llompart, Maria; Garcia‐Jares, Carmen; Dagnac, Thierry
Abstract: Four different miniaturized methodologies were developed and applied to the analysis of 11 UV filters in sand samples. These approaches were based on ultrasound and vortex extractions, on‐column lixiviation, and ultrasound extraction followed by solid‐phase microextraction. Gas chromatography with tandem mass spectrometry was used for quantitative analysis. The analytical performance provided by the four methods was evaluated in terms of linearity, accuracy, precision, and limits of quantification. Lixiviation was discarded since it provided the lowest recoveries and the highest limits of quantification. In contrast, ultrasound and vortex extractions, and ultrasound extraction followed by solid‐phase microextraction were suitable, with recoveries in general >85% and limits of quantification at the low ng/g level. Moreover, ultrasound extraction followed by solid‐phase microextraction allowed using external calibration with aqueous standards and it provided higher sensitivity, with limits of quantification in general one order of magnitude lower than those achieved with the other techniques. The methodologies were applied for the analysis of four marine sand samples, and the results were statistically compared performing an analysis of variance. Eight out of the eleven target UV filters were detected. Octocrylene was found at very high concentrations (up to 1000 ng/g) followed by ethylhexyl salicylate, 4‐methylbenzylidene camphor, homosalate, and 2‐ethylhexyl methoxycinnamate.